Panorama mapping of the colon - a phantom study with robotic endoscopy - Hackner, Ralf; Eixelberger, Thomas; Wittenberg, Thomas (Current Directions in Biomedical Engineering, 2022)
When documenting colonoscopic examinations, the challenge arises, that the exact location of the detected lesions (such as polyps) can usually only be determined with low precision. In order to improve the image-based documentation of such lesions with respect to their location and context, a system is currently investigated and developed, allowing the creation of a panoramic map of the interior of the colon's lumen during an endoscopic examination. To evaluate the proposed algorithms, a 3D-printed colon phantom with known geometry has been developed. Furthermore, to obtain image sequences with precise and known motion during a simulated examination for test purposes, a robot was used to perform the insertion and withdrawal of the endoscope with constant speed and a steady viewing angle. The thus obtained image data is used to generate an ideal panoramic map using our the proposed stitching algorithm. Hence, it is possible to obtain reference maps of the phantom, which can be used to evaluate the quality of the algorithm.
Created from Fastlane, Scopus look-up
Keywords: additive manufactured phantom; Endoscopy; panorama mapping; robot guided endoscopy